Finite Element Modeling of Composite Materials using Kinematic Constraints (2009)
The purpose of this article is to present simulations of the behavior of composite materials based on kinematic restrictions between the same fibers and between the fibers and the surrounding resin. In the literature review, the authors have found that kinematic restrictions have not been fully exploited to model composite materials, probably due to their high computational cost. The purpose of this article is to expose the implementation and results of such a model, using Finite Element Analysis of prescribed geometric constraints to the resin and fiber nodes. Analytical descriptions of the behavior of composite materials rarely appear. Many approaches to describe composite materials in layers are based on the theory of functions C1Z and C0 Z, such as the Classical Layer Theory (CLT). These theories of functions contain significant simplifications of the material, especially for woven compounds. A hybrid approach to modeling composite materials with Finite Elements (FEA) was developed by Sidhu and Averill and adapted by Li and Sherwood for composite materials woven with glass polypropylene.